Core competencies for international mobility for teachers and students in higher education - Evridiki Patelarou; Alexandra Trivli; Vladimir Đorđević; Stelios E. Papadakis; Giorgos M. Papadourakis; Alkinoos- Ioannis Zourmpakis; Maria Ampartzaki; Michaela Menšíková; Nada B. Ljubišić; Michail Kalogiannakis; Athina Patelarou (Population Medicine)
Introduction Consensus on the international mobility (IM) competencies for students and teachers has not yet been achieved in the European context. We aimed to establish a set of core IM competencies essential for effective internationalization and mobility, and make suggestions for their implementation among higher education institutions in European countries.